Extracorporeal Cardiopulmonary Resuscitation (ECPR) in Infants and Children: A Single-Center Retrospective Study. Issue 5 (September 2019) - Shakoor, Aqsa; Pedroso, Felipe E.; Jacobs, Shimon E.; Okochi, Shunpei; Zenilman, Ariela; Cheung, Eva W.; Middlesworth, William
Background: Extracorporeal cardiopulmonary resuscitation (ECPR) is increasingly used to rescue patients with cardiac arrest refractory to conventional therapy, necessitating evaluation of factors that may affect outcomes. Methods: A single-center retrospective review of pediatric patients (<21 years old) who underwent ECPR from January 2010 to November 2017. Comparisons between nonsurvivors and survivors, to decannulation and discharge, were made. Factors associated with survival and rate of complications were examined. Results: Seventy patients were supported with ECPR. Forty-nine (70%) patients survived to decannulation and 38 (54%) patients to discharge. There was no statistical difference between baseline characteristics of survivors and nonsurvivors, including age at cannulation, weight (kg), time to cannulation (minutes), and total time on extracorporeal membrane oxygenation (hours). Survivors to discharge had significantly higher pH prior to cannulation compared to nonsurvivors (7.11 ± 0.24 vs 6.97 ± 0.21, P = .01). Of all, 23.2% of patients received renal replacement therapy (RRT), 39.4% had significant bleeding, 22.5% had thrombotic complications, and 68.8% had neurologic injury on imaging studies. A greater number of nonsurvivors received RRT compared to survivors to discharge (35.5% vs 10.8%, P = .02). There were no differences in bleeding or thrombotic complications or radiographically established neurologic injury. Conclusions: Although ECPR effectively increases overall survival, a better characterization of long-term outcomes is needed.